2021
DOI: 10.1101/2021.03.10.21253280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of headache disorders on COVID-19 survival: a world population-based analysis

Abstract: Importance: COVID-19 has not impacted people or countries uniformly. This disparity has prompted investigations to identify clinical and genetic predictors of COVID-19 mortality. Headache, a COVID-19 symptom, has been associated with positive disease prognosis. It is logical to consider whether primary headache disorders, among the most prevalent and disabling diseases globally, may also be associated with reduced viral mortality and thereby may have arisen as adaptive host defences. Objective: To study the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
2
7
0
1
Order By: Relevance
“…Further, self-ratings of general health and autonomic-anxiety symptoms were worse amongst the 22 respondents who thought they had been infected with Covid-19, compared to those who had not been infected. The changes reported by our sample are consistent with reports of audio-vestibular symptoms in confirmed Covid-19 cases [17], as well as complex interactions between Covid-19 and pre-existing neurological conditions including migraine [16], where there is a higher likelihood of Covid symptomology and reduced wellbeing.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Further, self-ratings of general health and autonomic-anxiety symptoms were worse amongst the 22 respondents who thought they had been infected with Covid-19, compared to those who had not been infected. The changes reported by our sample are consistent with reports of audio-vestibular symptoms in confirmed Covid-19 cases [17], as well as complex interactions between Covid-19 and pre-existing neurological conditions including migraine [16], where there is a higher likelihood of Covid symptomology and reduced wellbeing.…”
Section: Discussionsupporting
confidence: 89%
“…Signs of peripheral and central nervous system complications (e.g., encephalopathy, stroke, seizures) and neurological symptoms (e.g., anosmia, headache) have been reported during and after the Covid-19 infection [13] with vertigo, dizziness, tinnitus and hearing loss [2,14] commonly described. Another important problem is the finding that those with a history of migraine, a disorder commonly accompanied by vestibular symptomology, appear to have a higher likelihood of Covid-19 infection, and subsequently report more frequent symptoms than those without migraine [15,16]. As yet, the causes and origins of these vestibular problems are unclear; Covid-19 may directly damage the central nervous system and inner ear organs, or trigger systemic immune responses through a viral infection that affects the vestibular system less specifically [17].…”
mentioning
confidence: 99%
“…The presence of headache has been associated with better COVID-19 evolution in terms of 1-week shorter COVID-19 disease duration [13•] and was inversely associated with worse outcomes in one study involving 1000 patients attended at the ER [23]. Two studies also observed that headache was associated with lower mortality [12•], findings confirmed by a recent meta-analysis showing a significantly higher risk ratio of survival COVID-19 in patients with headache [24].…”
Section: Prognosismentioning
confidence: 80%
“…Investigating primary headache disorders in the context of a viral infection will be even more relevant in the future, considering that COVID-19 studies have observed that headache as a symptom of the acute phase of the infection is associated with lower mortality. It is therefore logical to wonder whether primary headache disorders as well may be protective in viral infections [24]. In that case, questions may raise on whether they have emerged as adaptive responses in human evolution to enhance survival and consequently genetically selected in the population in response to certain stimuli such as viruses [24].…”
Section: Primary Headache Disorders In the Context Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation